2020
DOI: 10.1186/s12887-020-02393-2
|View full text |Cite
|
Sign up to set email alerts
|

Where the congenital heart disease meets the pulmonary arterial hypertension, FLNA matters: a case report and literature review

Abstract: Background Pediatric patients with genetic disorders have a higher incidence of pulmonary arterial hypertension (PAH) regardless of their heart defects. Filamin A (FLNA) mutation is recently recognized to be associated with pediatric pulmonary disorders, however, the clinical courses of PAH related to the mutation were reported in limited cases. Here, we presented a case and pooled data for better understanding of the correlation between FLNA mutation and pediatric PAH. Case presentation The patient was a 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Mutations in FLNA can cause variable clinical features, including neurological, skeletal and cardiac dysfunction. Several reports have indicated that patients with FLNA mutations present with severe diffuse lung disease and severe pulmonary hypertension (23,24). Masurel-Paulet et al (25) reported that a male patient with a mosaic nonsense FLNA mutation presented with PAH and severe lung manifestations, and lung histology showed pan-pulmonary emphysema with a marked reduction of bronchial cartilage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in FLNA can cause variable clinical features, including neurological, skeletal and cardiac dysfunction. Several reports have indicated that patients with FLNA mutations present with severe diffuse lung disease and severe pulmonary hypertension (23,24). Masurel-Paulet et al (25) reported that a male patient with a mosaic nonsense FLNA mutation presented with PAH and severe lung manifestations, and lung histology showed pan-pulmonary emphysema with a marked reduction of bronchial cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Hirashiki et al (9) reported that a family with heritable PAH carried a novel heterozygous splicing mutation in the FLNA gene. deng et al (23) summarized 19 pediatric cases with FLNA mutation; these patients presented with early onset PAH and all cases were complicated with congenital heart disease. Sasaki et al (26) summarized 18 cases of FLNA mutation and interstitial lung disease (ILD), 14 of which had PAH.…”
Section: Discussionmentioning
confidence: 99%
“…It promotes orthogonal branching of actin filaments and links actin filaments to membrane glycoproteins with wide tissue expression. FLNA mutations can cause several severe syndromes, including periventricular nodular heterotopias, otopalatodigital syndromes, skeletal dysplasia, lung involvement, and cardiovascular abnormalities (Sankararaman et al, 2013;van der Werf et al, 2013;Deng et al, 2020;Meliota et al, 2021). In heterozygous females, the FLNA-related phenotype ranges from the absence of overall symptoms to severe manifestations.…”
Section: Discussionmentioning
confidence: 99%